Stress-related growth in elite sport performers: qualitative differentiators in psychosocial mechanisms - Barnes, F. B.; Fletcher, D.; Neely, K. C. (The Sport Psychologist, 2021)
The purpose of this study was to explore growth following the experience of stressors and compare the experiences of elite athletes who exhibit higher and lower levels of growth. Six elite athletes (five female and one male) participated in a semi-structured interview. Three athletes reported experiencing higher levels, and three athletes reported experiencing lower levels of growth. Interpretative phenomenological analysis revealed that understanding of self, development in athletic identity, and social support are key psychological mechanisms, which differentiate elite athletes who reported experiencing higher and lower levels of growth. Athletes higher in reported growth showed greater association with meaningful behavioral actions, ultimately reflecting the modification of previously held beliefs into a new worldview. Athletes lower in reported growth reflected an attempt to maintain beliefs into an already existing worldview, thus hindering growth. The findings show psychological mechanisms that accumulatively promote growth and provide a foundation for subsequent intervention studies.